Silver Nanowires as Electron Transfer Mediators in Electrochemical Catechol Biosensors - Salvo-Comino, Coral (Sensors (Basel), 2021)
The integration of nanomaterials as electron mediators in electrochemical biosensors is taking on an essential role. Due to their high surface-to-volume ratio and high conductivity, metallic nanowires are an interesting option. In this paper, silver nanowires (AgNWs) were exploited to design a novel catechol electrochemical biosensor, and the benefits of increasing the aspect ratio of the electron mediator (nanowires vs. nanoparticles) were analyzed. Atomic force microscopy (AFM) studies have shown a homogeneous distribution of the enzyme along the silver nanowires, maximizing the contact surface. The large contact area promotes electron transfer between the enzyme and the electrode surface, resulting in a Limit of Detection (LOD) of 2.7 × 10(−6) M for tyrosinase immobilized onto AgNWs (AgNWs-Tyr), which is one order of magnitude lower than the LOD of 3.2 × 10(−5) M) obtained using tyrosinase immobilized onto silver nanoparticles (AgNPs-Tyr). The calculated K(M) constant was 122 mM. The simultaneous use of electrochemistry and AFM has demonstrated a limited electrochemical fouling that facilitates stable and reproducible detection. Finally, the biosensor showed excellent anti-interference characteristics toward the main phenols present in wines including vanillin, pyrogallol, quercetin and catechin. The biosensor was able to successfully detect the presence of catechol in real wine samples. These results make AgNWs promising elements in nanowired biosensors for the sensitive, stable and rapid voltammetric detection of phenols in real applications.